Optimalisasi Zakat Produktif dalam Pemberdayaan UMKM - Arsyad, Adnan; Harifuddin, Didin; Ayuniyyah, Qurroh (Universitas Islam Negeri Alauddin Makassar, 2023)
The aim of this research is to determine the productive zakat distribution model for the empowered village program carried out by Rumah Zakat and to determine its effect on empowering MSMEs in the assisted villages. In terms of methodology, this research uses a qualitative approach method, with the data sources used being primary and secondary sources. Data collection techniques are carried out by observation and interviews and data analysis is carried out using data reduction techniques, data display and drawing conclusions. The results of this research found that Rumah Zakat's productive zakat distribution model in the villages supported by Kel. Cipinang Muara East Jakarta is carried out in five stages which include area mapping, mustahik data collection, mentoring, training and coaching which provides business consulting services, guidance on using digital media, marketing networks, online product promotion, how to carry out transactions, and providing advertising media. The independent smile program provided by Rumah Zakat through digitalization of MSMEs has had a significant positive influence in empowering mustahik MSMEs in the assisted villages in Kel. Cipinang Muara, East Jakarta, this can be seen from the increase in their sales turnover after receiving assistance.